Validation of the XDP–MDSP rating scale for the evaluation of patients with X-linked dystonia-parkinsonism - Paul Matthew D. Pasco; Roland Dominic G. Jamora; Raymond L. Rosales; Cid Czarina E. Diesta; Arlene R. Ng; Rosalia A. Teleg; Criscely L. Go; Lillian Lee; Hubert H. Fernandez (npj Parkinson's Disease, 2017)
Disease rating scale: Adressing a Philippine problem Researchers validate a tool to assess patients with X-linked dystonia parkinsonism (XDP), a movement disorder that affects men of Filipino descent. Roland Dominic Jamora and Paul Matthew Pasco, at the University of the Philippines Manila, and colleagues collaborated with the Movement Disorder Society of the Philippines (MDSP) to develop a new comprehensive rating scale that is specific for this condition. The 37-item test was administered to over 200 patients and the results correlated with those obtained in commonly used scales for the assesment of dystonia, parkinsonism, motor and non-motor symptoms. The authors conclude that the XDP-MDSP rating scale will allow clinicians and researchers to evaluate the severity of XDP as well as determine patients’ response to treatment. Further refining the scale may be required to discern the effect of patients’ anxiety and depression on their functional state.